SDLC Big Bang dan Waterfall : Perbandingan Pendekatan dalam Pengembangan Perangkat Lunak - Evi Dwi Wahyuni; Firdatul Nurul Ramadha; Defan Deo Vannes (FKOM UNIKU, 2024)
The development of software necessitates the selection of appropriate methodologies to ensure effectiveness and quality. This research aims to assess the strengths and weaknesses of the Big Bang and Waterfall methodologies through the analysis of diverse case studies. The Big Bang approach allows teams to begin work swiftly without detailed initial planning, yet it often results in products with inconsistent quality and susceptibility to bugs. Conversely, the Waterfall method provides a structured, sequential approach but lacks flexibility in accommodating changes. Choosing the right methodology should be tailored to meet the specific needs and characteristics of each project. It is essential for professionals to have a comprehensive understanding of each methodology to increase the likelihood of success in software development. This study lays a robust foundation for future advancements, emphasizing the importance of empirical research and exploring hybrid approaches.